ANALYSIS OF THE IMPACT OF VOLTAGE IMBALANCE ON THE PERFORMANCE OF A MICROCONTROLLER-BASED CAGE ROTOR INDUCTION MOTOR - Abdullah Avif Putra Buana; Ruskardi; Rianda (Universitas Tarumanagara, 2025)
The three-phase induction motor is the most widely used alternating current (AC) electric motor in industrial applications, particularly for driving large-capacity loads. Its flexibility, efficiency, and ability to operate reliably under harsh environmental conditions make it the preferred choice in manufacturing, processing, and mining sectors, with an estimated 70% share of all industrial electric machines. However, one common technical issue encountered in the field is three-phase supply voltage unbalance. Even a small percentage of voltage unbalance can lead to increased phase current, torque fluctuations, higher operating temperatures, reduced efficiency, and instability in the overall power system. This study aims to analyze the impact of voltage unbalance on the performance of a squirrel-cage induction motor using a microcontroller-based monitoring system. Laboratory experiments were conducted by varying the degree of voltage unbalance in accordance with the NEMA MG 1-1993 standard. The monitoring system was designed with a microcontroller integrated with voltage and current sensors, enabling real-time data acquisition. The measured parameters included current, speed, slip, torque, and efficiency. Experimental results indicate that increasing the voltage unbalance from 0.53% to 5.22% led to a 4–7-fold increase in current unbalance, a slip rise of approximately 2%, and a reduction in efficiency from 90% to 82%. These findings demonstrate a direct correlation between supply voltage quality and motor performance. The results emphasize that controlling voltage unbalance—whether through proper distribution system maintenance or the use of compensation devices—is essential to maintaining optimal performance and extending the service life of three-phase induction motors in industrial environments. Motor induksi tiga fasa merupakan motor listrik arus bolak-balik (AC) yang paling banyak digunakan di industri, terutama sebagai penggerak beban berkapasitas besar. Fleksibilitas, efisiensi, dan ketahanannya terhadap kondisi lingkungan yang berat menjadikannya pilihan utama pada sektor manufaktur, pengolahan, dan pertambangan, dengan estimasi penggunaan mencapai 70% dari seluruh mesin listrik industri. Namun, salah satu permasalahan teknis yang sering ditemui di lapangan adalah ketidakseimbangan tegangan suplai tiga fasa. Ketidakseimbangan ini, meskipun hanya beberapa persen, dapat memicu kenaikan arus fasa, fluktuasi torsi, peningkatan suhu operasi, penurunan efisiensi, dan gangguan kestabilan sistem tenaga listrik. Penelitian ini bertujuan menganalisis dampak ketidakseimbangan tegangan terhadap performa motor induksi rotor sangkar menggunakan sistem monitoring berbasis mikrokontroler. Pengujian dilakukan di laboratorium dengan memvariasikan ketidakseimbangan tegangan sesuai standar NEMA MG 1-1993. Sistem monitoring dirancang menggunakan mikrokontroler yang terintegrasi dengan sensor tegangan dan arus, sehingga mampu merekam data secara real-time. Parameter yang diukur meliputi arus, kecepatan, slip, torsi, dan efisiensi. Hasil pengujian menunjukkan bahwa peningkatan ketidakseimbangan tegangan dari 0,53% hingga 5,22% menyebabkan ketidakseimbangan arus hingga 4–7 kali lipat, kenaikan slip sekitar 2%, serta penurunan efisiensi dari 90% menjadi 82%. Dampak ini menunjukkan korelasi langsung antara kualitas tegangan suplai dan kinerja motor. Temuan ini menegaskan bahwa pengendalian ketidakseimbangan tegangan, baik melalui pemeliharaan sistem distribusi maupun penggunaan perangkat kompensasi, sangat penting untuk mempertahankan performa optimal dan memperpanjang umur pakai motor induksi tiga fasa di lingkungan industri.